Diagnosis Code Accuracy Analysis Of Acute Gastroenteritis Disease Based on Medical Record Document in Balung Hospital Jember - Rinda Nurul Karimah; Dony Setiawan; Puput Septining Nurmalia (Journal of Agromedicine and Medical Sciences, 2016)
Accuracy analysis of replenishment diagnosis codes on the document medical records is very important because if the diagnosis code is not right or not in accordance with the ICD-10, it can cause a decline in the quality of care in hospitals as well as the influence of data, information reporting, and accuracy rates of INA-CBG's that are currently used as a method of payment for patient care. The purpose of this study was to analyze the accuracy of diagnosis codes acute gastroenteritis disease in hospitalized patients by medical record documents in the first quarter of 2015 in the Balung Hospital Jember. This research used qualitative data. Acquisition of data from this study through interviews and observations. Results obtained from the observation of medical record documents at the inpatient unit in the first quarter 2015 in Balung Hospital Jember, there are some numbers determining the accuracy of disease diagnosis codes as many as 17 medical record documents with acute gastroenteritis illness and the determination of improper diagnosis codes as many as 63 medical records document acute gastroenteritis illness. After analyzing, the cause of the problem is the accuracy of the diagnosis that affects the accuracy of writing code, beside it has never been disseminated to physicians and medical records personnel related to the management of medical records. Therefore, it is necessary to carry out activities that can improve the accuracy of disease diagnosis code and quality of human resources, among others, include doctors and medical records personnel in training and socialization related to the management of medical records. Key Words : Diagnosis codes , medical record, acute gastroenteritis